Functional characterization of SGLT1 using SSM-based electrophysiology: Kinetics of sugar binding and translocation - Bazzone, Andre; Zerlotti, Rocco; Barthmes, Maria; Fertig, Niels (Frontiers in Physiology, 2023)
Beside the ongoing efforts to determine structural information, detailed functional studies on transporters are essential to entirely understand the underlying transport mechanisms. We recently found that Solid Supported Membrane based electrophysiology (SSME) enables the measurement of both sugar binding and transport in the Na+/sugar cotransporter SGLT1 (Bazzone et al., 2022a). Here, we continued with a detailed kinetic characterization of SGLT1 using SSME, determining KM and KDapp for different sugars, kobs values for sugar-induced conformational transitions and the effects of Na+, Li+, H+ and Cl- on sugar binding and transport. We found that the sugar-induced pre-steady-state (PSS) charge translocation varies with the bound ion (Na+, Li+, H+ or Cl-), but not with the sugar species, indicating that the conformational state upon sugar binding depends on the ion. Rate constants for the sugar-induced conformational transitions upon binding to the Na+-bound carrier range from 208 s-1 for D-glucose to 95 s-1 for 3-OMG. In the absence of Na+, rate constants are decreased, but all sugars bind to the empty carrier. From the steady-state transport current, we found a sequence for sugar specificity (Vmax/KM): D-glucose > MDG > D-galactose > 3-OMG > D-xylose. While KM differs 160-fold across tested substrates and plays a major role in substrate specificity, Vmax only varies by a factor of 1.9. Interestingly, D-glucose has the lowest Vmax across all tested substrates, indicating a rate limiting step in the sugar translocation pathway following the fast sugar-induced electrogenic conformational transition. SGLT1 specificity for D-glucose is achieved by optimizing two ratios: the sugar affinity of the empty carrier for D-glucose is similarly low as for all tested sugars (KDapp=210 mM). Affinity for D-glucose increases 14-fold (KD,Naapp=15 mM) in the presence of sodium as a result of cooperativity. Apparent affinity for D-glucose during transport increases 8-fold (KM=1.9 mM) compared to KD,Naapp due to optimized kinetics. In contrast, KM and KDapp values for 3-OMG and D-xylose are of similar magnitude. Based on our findings we propose an 11-state kinetic model, introducing a random binding order and intermediate states corresponding to the electrogenic transitions detected via SSME upon substrate binding.